PLASMA EXCHANGE IN PATIENTS WITH THE DIAGNOSIS OF GUILLAIN-BARRE SYNDROME: AN EXPERIENCE IN INTENSIVE CARE UNIT - Ali, Gauhar; Kamal, Mustafa; Khan, Abdul Naseer (Journal of Postgraduate Medical Institute, 2011)
Objective: Methodology: Results: Conclusion: Early referral to Intensive Care Unit, management of complications, good nursing care and specific therapy with Plasma Exchange within seven days of onset of symptoms improve prognosis and Plasma Exchange has proved beneficial to supportive treatment alone in Guillain-Barre syndrome with minimal side effects. Out of 28 patients 19 were male (67.85%) and 9 were female (32.14%). Mean age was 32.32 years and mean duration of stay in Intensive Care Unit was 6.32 days. Out of these 28 patients, 60.71% (17) recovered and 39.3% (11) expired despite treatment and 2 patients developed adverse events secondary to Plasma Exchange. In 25 (89.29%) patients breathlessness was reported as their major symptom beside motor weakness, while in 19 (67.85%) patients, pain was also reported. This descriptive study was conducted at Intensive Care Unit Lady Reading Hospital Peshawar from March 2008 to July 2010. Twenty eight patients were included in study after fulfilling inclusion criteria. All the diagnosed cases of Guillain-Barre syndrome were admitted in Intensive care Unit Post Graduate Medical Institute Lady Reading Hospital Peshawar and 4 sessions of plasma Exchange therapy was initiated in every patient after informed written consent. To assess the effectiveness of plasma exchange in patients with Guillain-Barre syndrome.